When a Little Does a Lot: How Dilute Alloying Can Stabilize Catalysts for More Efficient Chemical Reactions. - Dannar, Audrey. (Tufts University. Tisch Library., 2022)
Heterogeneous catalysts are involved in the production of over $10 trillion of products annually and are thus critical for daily life as we know it. Because of the massive scale of catalysis, small developments and optimizations can offer significant environmental and financial benefits. One place for optimization is improving the stability of catalysts by mitigating their deactivation. Sintering is one of the major mechanisms of catalyst deactivation which involves the coalescence of the nano-sized catalyst particles. Dilute alloys such as Single-Atom Alloys (SAA) are known to resist sintering but this boost in stability is not currently understood. SAAs are composed of a selective host metal with ~1% of the surface embedded with atoms of more active dopant metal. Using scanning tunneling microscopy (STM), I show that single Pt atoms in a 110 facet of a copper step edge significantly stabilize step edges from room temperature to 390 K. Using Cu and PtCu as model systems, I am developing a atomic-level understanding the sintering resistance empirically observed for SAA catalysts and predicting sintering resistance in new materials. My results depict an atomic-scale view of a major mechanism of catalyst deactivation, and a rationalization for the surprising observation that only a tiny amount of dopant can change and improve the properties of the catalyst as a whole.; 15-minute talk presented at the Tufts Graduate Student Council's 27th Graduate Student Research Symposium, April 20, 2022.